2002
DOI: 10.3346/jkms.2002.17.5.604
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Burden of Major Cancers in Korea

Abstract: We estimated the burden of diseases in Korea especially caused by major cancers using DALY (disability adjusted life year) measurement. Firstly, the burden of disease due to premature death was estimated by using YLLs (years life lost due to premature death) measurement developed by the global burden of disease study group. Secondly, for the calculation of the YLD (years lived with disability), the following parameters were estimated in the formula; incidence rate, case fatality rate and disability weight of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 14 publications
3
30
0
1
Order By: Relevance
“…The first national BoD study in Korea using the DALY metric was presented in 2002 (12), and many diverse BoD studies have been conducted since (1314151617181920212223242526272829303132333435). The DALY concept, however, is primarily used academically and has not yet been actually utilized in the health policy arena.…”
Section: Introductionmentioning
confidence: 99%
“…The first national BoD study in Korea using the DALY metric was presented in 2002 (12), and many diverse BoD studies have been conducted since (1314151617181920212223242526272829303132333435). The DALY concept, however, is primarily used academically and has not yet been actually utilized in the health policy arena.…”
Section: Introductionmentioning
confidence: 99%
“…The methods used in this analysis have been extensively described and documented in the peer-reviewed literature on the measurement of the burden of disease [6][7][8][9][10][11][12][13][14][15] . Mortality data for the USA for the year 2001 were obtained from the National Center for Health Statistics website (http://www.cdc.gov/nchs).…”
Section: Methodsmentioning
confidence: 99%
“…It has been considered to be less common among Asians and Caucasians [6,7] . However, recent studies have shown an increasing trend in these populations [8][9][10] . Variation in the incidence of colorectal neoplasia has been observed in populations and even in cities of one country.…”
Section: Introductionmentioning
confidence: 99%